Forward to the past: Short-term effects of the rent freeze in Berlin - Anja M. Hahn; Konstantin A. Kholodilin; Sofie Waltl (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
In 2020, Berlin enacted a rigorous rent-control policy: the 'Mietendeckel' (rent freeze), aiming to stop rapidly growing rental prices. We evaluate this newly enacted but old-fashionably designed policy by analyzing its immediate supply-side effects. Using a rich pool of rent advertisements reporting asking rents and comprehensive dwelling characteristics, we perform hedonic-style Difference-in-Difference analyses comparing trajectories of dwellings inside and outside the policy's scope. We find no immediate effect upon announcement of the policy. Yet advertised rents drop significantly upon the policy's enactment. Additionally, we document a substitution effect affecting the rental markets of Berlin's (unregulated) satellite city Potsdam and adjacent smaller municipalities. On top, the supplemental quantity analyses reveal a stark reduction of the number of advertised rental units hampering a successful housing search for newcomers, (young) first-time renters and tenants aiming for a different housing opportunity.
Keywords: C14; C43; O18; 330; First-Generation Rent Control; Rent Freeze; Urban Policy; Rent Price; Supply Disruptions; Berlin